Pattern of follicular development in sheep subjected to ovarian superstimulation after follicular ablation by laparoscopic ovum pick-up - Denadai,Renan (2017)
ABSTRACT: The aim of this study was to determine the pattern of follicular development in ewes following ablation of all follicles associated with ovarian superstimulatory treatment. After confirmation of reproductive cyclicity using ultrasonography and progesterone levels, five adult ewes of undetermined breed received a vaginal pessary containing 60mg of medroxyprogesterone, maintained for 10 days, with the application of 100μg cloprostenol on the fourth day. On the tenth day, 300UI equine chorionic gonadotropin (eCG) was applied together with 80mg FSH, and all visible follicles were aspirated by laparoscopic ovum pick-up (LOPU). Following LOPU, ovarian structures were assessed using sonography every 8 hours for a period of 64 hours, and the number and diameter of small (<2.5mm), medium-sized (2.5-4.5mm), and large (>4.5mm) follicles were recorded. The average diameter of small follicles reduced from 5.6±1.5mm initially to 0.8±1.3mm by 56 hours. Population size of the medium-sized follicles during the observation period followed a parabolic distribution wherein the theoretical maximum size emerged at 34.6 hours with no difference at (P>0.05) 24 (4.6±1.5) and 48 hours (4.8±2.3). It was concluded that in ewes subjected to ovarian superstimulation immediately following LOPU, follicular development is characterized by a new wave of follicle growth with a predominance of medium-sized follicles (2.5-4.5mm) between 24 and 48 hours, and a theoretical population maximum occured at 34.6 hours.